1952
DOI: 10.1113/expphysiol.1952.sp000989
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulin on the Secretion of Gastric Juice in the Goat

Abstract: 1. In goats provided with innervated pouches of the abomasum, the intramuscular injection of insulin was followed by a depression of volume‐rate and of the free and total acidity of the secretion. 2. No relation was observed between the degree of hypoglycæmia and the depression of gastric secretion, or between the degree of hypoglycæmia produced by a given dose of insulin and the previous duration of fasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1954
1954
1989
1989

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The demonstration of a secretory response to insulin hypoglycaemia was at variance with previous results obtained in the lamb (Hitchcock et al 1948) and in the goat (Hill, 1952b), where inhibition of secretion was noted. The reason for this discrepancy is not known but the over-secretion which occurred in the present experiments when the reticulo-rumen contained food material indicated that the vagi exert considerable control over the gastric glands.…”
Section: Discijssioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The demonstration of a secretory response to insulin hypoglycaemia was at variance with previous results obtained in the lamb (Hitchcock et al 1948) and in the goat (Hill, 1952b), where inhibition of secretion was noted. The reason for this discrepancy is not known but the over-secretion which occurred in the present experiments when the reticulo-rumen contained food material indicated that the vagi exert considerable control over the gastric glands.…”
Section: Discijssioncontrasting
confidence: 56%
“…The effect of vagal stimulation on abomasal secretion Vagal stimulation brought about by insulin hypoglycaemia has been employed extensively in studies in gastric secretion (see Bachrach, 1953) and although previous investigations (Hitchcock, Karvonen & Phillipson, 1948;Hill, 1952b) had indicated that insulin hypoglycaemia was inhibitory to abomasal secretion it was deemed worth while to reinvestigate this point.…”
Section: The Flow Of Ingesta During Feedingmentioning
confidence: 99%
“…Although established as a means of testing the integrity of the vagal innervation of fundic pouches in the dog (Jemerin, Hollander & Weinstein, 1943) it has not been used definitively in ruminants in which its effects on antral exocrine secretion do not appear to have been studied: in other species antral endocrine (gastrin) secretion is increased during insulin hypoglycaemia (Jaffe, McGuigan & Newton, 1970). Hill (1952) found reductions in acid secretion of abomasal pouches of the goat during insulin hypoglycaemia and in other experiments Hill (1968) found a stimulation of fundic acid secretion associated with reticulo-ruminal hypermotility. 20 00 secretion in a sheep (4) following the sxc.…”
Section: Resultsmentioning
confidence: 79%